Essays in contextual theology - Bevans, Stephen B., 1944- (Theology and Mission in World Christianity, 2018)
Essays in Contextual Theology is a collection of essays that reflect on the doing of contextual theology from several perspectives. After a general introductory essay, subsequent essays reflect on topics such as contextual theology and prophetic dialogue, criteria for orthodoxy, the nature of tradition, the role of culture, the dynamics of conversion, and the way theology is being done in World Christianity. The collection closes with an autobiographical essay tracing the author's journey to becoming a "global theologian."